Revitalizing the Pojok Literasi at SDN 1 Mangkujayan: Addresing the Challenges of Reading Interest in the Digital Era - Hidayati, Lailatul; Yanti, Yuni Widya; Habibi, Mukhlas (Proceeding International Conference on Religion, Science and Education, 2025)
The revitalization of the Pojok Literasi in elementary schools is a crucial effort to increase students' interest in reading, especially in the digital era filled with distractions. This research aims to explore how the revitalization of the Pojok Literasi at SDN 1 Mangkujayan can address the challenge of low reading interest among students. Using a descriptive qualitative approach and a case study method, this study involves interviews with teachers, students, and school administrators, as well as direct observations of activities in the Pojok Literasi. Data analysis includes reduction, presentation, and conclusion drawing. The results indicate that the revitalization efforts include: (1) designing an attractive Pojok Literasi, (2) arranging the bookshelves neatly, (3) providing dedicated time to explore the Pojok Literasi, and (4) adding engaging fiction and nonfiction books. However, several challenges were encountered, such as a lack of parental support and insufficient updates of books from the school. Despite these obstacles, the Pojok Literasi has gradually increased students' interest in reading, particularly through the applied interactive and innovative approaches. This is evident from students' enthusiasm to read independently and joyfully, without prompting. This study concludes that the revitalization of the Pojok Literasi at SDN 1 Mangkujayan effectively addresses the challenge of reading interest in the digital era, though further improvement in collaboration between schools and parents is necessary to maximize students' reading engagement.